2014
DOI: 10.1007/s12282-014-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of HER2 gene status assessment by fluorescence in situ hybridization between histological sections and cytological specimens of breast cancer

Abstract: FISH-based assessment of the HER2 gene status is consistent between histological sections and cytological specimens of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, multiple studies have repeatedly shown that FNAB samples provide reliable biomarker information, with high concordance rates (>90%) for estrogen receptor (ER), progesterone receptor (PR), and HER2 results when compared with subsequent excision specimens. [48][49][50][51][52][53] In addition, the ASCO/College of American Pathologists guideline recommendations accept FNAB as a source of breast cancer biomarker information, further supporting FNAB use for this clinical purpose. 54,55 In the MGH-FNAB group, 6 of 7 malignant FNAB patient samples tested for ER, PR, and HER2 were entirely concordant with the results derived from the subsequent excisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple studies have repeatedly shown that FNAB samples provide reliable biomarker information, with high concordance rates (>90%) for estrogen receptor (ER), progesterone receptor (PR), and HER2 results when compared with subsequent excision specimens. [48][49][50][51][52][53] In addition, the ASCO/College of American Pathologists guideline recommendations accept FNAB as a source of breast cancer biomarker information, further supporting FNAB use for this clinical purpose. 54,55 In the MGH-FNAB group, 6 of 7 malignant FNAB patient samples tested for ER, PR, and HER2 were entirely concordant with the results derived from the subsequent excisions.…”
Section: Discussionmentioning
confidence: 99%
“…Bozzetti et al found a 91% concordance rate between HER2 FISH results in FNA smears compared with surgical pathology specimens, and a 92% concordance rate between HER2 FISH and IHC results in cytology smears . Recently, HER2 amplification by FISH has been investigated using LBC (PreservCyt): FISH was possible in 98 of 100 LBC specimens and concordant with surgical pathology FISH results in 97 of those 98 cases …”
Section: Comparison Between Detection Methods For Her2 Overexpressionmentioning
confidence: 99%
“…22 Recently, HER2 amplification by FISH has been investigated using LBC (PreservCyt): FISH was possible in 98 of 100 LBC specimens and concordant with surgical pathology FISH results in 97 of those 98 cases. 23 Next-generation sequencing (NGS) offers the opportunity to assess HER2 copy number status and HER2 mutations simultaneously, along with other molecular events such as tumor mutation burden and microsatellite instability status. NGS can be performed on both surgical pathology specimens or cell blocks, and it recently has been shown to work well on cytologic supernatant material.…”
mentioning
confidence: 99%
“…The quantification of hybridized marker probes is commonly done by microscopic visualization of hybridization spots and manual counting of those spots on a single‐cell level. Alternatively, the identification of cells (within a tissue) and the FISH signal counting can be performed (semi‐)automatically using sophisticated software and imaging systems (Knudson et al., 2007; Martinez et al., 2013; Narath et al., 2004; Nishimura et al., 2016; Smith et al., 2010; Zwaenepoel et al., 2015). Automated cell imaging and analyses have been successfully applied using systems developed and distributed, for example, by BioView (http://www.bioview.com) or Metasystems (http://www.metasystems-international.com).…”
Section: Introductionmentioning
confidence: 99%